Future Bleak for Rohingya in Bangladesh, Myanmar - Human Rights Watch (Human Rights Watch, 2023)
One million Rohingya refugees in Bangladesh face little prospect of safely returning home, six years since the Myanmar military launched a campaign of mass atrocities in Rakhine State on August 25, 2017.
Keywords: 2023-07 July; Refugees; Rohinga